The Implications of Social Media Use on Household Harmony: An Analysis of Divorce Rates in Wajo Regency - Ismail Arsyad; Sudirman L; Islamul Haq (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
The advancement of digital technology has transformed patterns of human communication, including interactions within the household. Social media, originally intended for social connection and entertainment, has increasingly become a source of marital tension. Online infidelity, emotionally intimate digital communication, jealousy arising from virtual interactions, and violations of digital privacy often develop into prolonged conflicts that threaten marital stability. This study examines the contribution of social media to divorce cases at the Sengkang Religious Court, analyzes judicial legal reasoning in such cases, and interprets the phenomenon through the perspective of Islamic jurisprudence. A qualitative case-study approach was employed, involving document analysis, courtroom observation, and in-depth interviews with judges, clerks, and litigants. Data from 2024 show that out of 1,011 divorce cases, approximately 20 percent explicitly involved conflicts related to social media use, indicating a significant impact of digital behavior on marital dissolution. Judicial considerations are primarily based on Article 19(f) of Government Regulation No. 9/1975 and Article 116(f) of the Kompilasi Hukum Islam, which recognize continuous disputes (syiqaq) as lawful grounds for divorce. Judges evaluate not only formal digital evidence, such as screenshots and message records, but also the psychological and emotional harm caused by digital misconduct. Mandatory mediation under Supreme Court Regulation No. 1/2016 is used to assess the possibility of reconciliation. From the perspective of Islamic law, harmful social media practices are assessed through the maxim dar’ al-mafāsid muqaddam ‘alā jalb al-maṣāliḥ, affirming that divorce is permissible when digital harm outweighs marital benefit.